PEMAKAIAN HIDDEN BEVEL LENSA CR-39 DENGAN AUTO GROOVER DAN KENYAMANAN PENGGUNA - Andriani; Wahyu Budiana; Opep Cahya Nugraha; Nisa Zakiati Umami (Jurnal Mata Optik, 2020)
Bevel Hidden manufacture lenses CR - 39 in optical dispensing laboratories using Autogroover engine requires high precision and skills so as to produce glasses that fit the patient's wishes, in this paper the author uses descriptive method of literature data one by David Wilson with the title of the book "Practical Optical Dispensing" bifocal lens that can focus both horizontally and can be completed in a placement center vertically so as to produce a lens with good quality